Cultivars of Ocañera onion (Allium cepa L.) under protected and open-field conditions - Rosero-Alpala, María Gladis (2024)
Introduction. Evaluating onion cultivars (Allium cepa L.) in different environments to understand their adaptation is important due to the crop’s relevance in food supply across various countries, the reduction in its genetic diversity, the loss of beneficial traits, and resistance to diseases and pests. Objective. To assess the agronomic performance of onion cultivars under different environments to identify the best ones in terms of adaptation, yield, and interaction. Materials and methods. From November 2017 to August 2018, at the La Selva Research Center of the Corporación Colombiana de Investigación Agropecuaria (AGROSAVIA), Rionegro, Antioquia, Colombia, twenty-one onion cultivars plus two controls were evaluated: Peruana of the Aggregatum group and Yellow Granex of the Cepa, under open-field and protected conditions with plastic roofing, using multilocation trials in a randomized complete block design and four replications. Evaluations were consucted on categories such as bulb weight, number, length, and diameter, along with the interaction of cultivars and environments. Results. In othe open field, due to lower temperatures compared to those recorded under protected conditions resulted in higher yields of weight and number of bulbs. Under protected environments, Aggregatum group cultivars behaved as if they were from the Cepa group, producing fewer large-size bulbs. The adaptation of cultivars varied by environment: in the open field, L55 and L63 cultivars exhibited the best yields, while under protected conditions, RPT20 and RPT11 showed the best adaptation. Conclusion. Environments significantly influenced the behavior of Aggregatum group cultivars, with higher production of extra-large bulbs. Temperature contrasts in protected enviroments with plastic roofing affected cultivars yields, while open-field conditions were more favorable.